Ethical hacking - Alana Maurushat (University of Ottawa Press, 2019)
How will governments and courts protect civil liberties in this new era of hacktivism? Ethical Hacking discusses the attendant moral and legal issues. The first part of the 21st century will likely go down in history as the era when ethical hackers opened governments and the line of transparency moved by force. One need only read the motto "we open governments" on the Twitter page for Wikileaks to gain a sense of the sea change that has occurred. Ethical hacking is the non-violent use of a technology in pursuit of a cause-political or otherwise-which is often legally and morally ambiguous. Hacktivists believe in two general but spirited principles: respect for human rights and fundamental freedoms, including freedom of expression and personal privacy; and the responsibility of government to be open, transparent and fully accountable to the public. How courts and governments will deal with hacking attempts which operate in a grey zone of the law and where different ethical views collide remains to be seen. What is undisputed is that Ethical Hacking presents a fundamental discussion of key societal questions.
hdl:10393/39080
Keywords: 300; Datensicherheit; Ethik; Grundrecht; Meinungsfreiheit; Whistleblowing